Vitamin D Receptor Expression Is Significantly Decreased in Bone Metastases Compared to Matched Primary Breast Cancer Tumours. (7th February 2023) - Horas, Konstantin; Abraham, Marc; Ebert, Regina; Weissenberger, Manuel; Maier, Gerrit S.; Jakob, Franz; Rosenwald, Andreas; Rudert, Maximilian
Abstract: There is ample evidence today that vitamin D signalling via the vitamin D receptor (VDR) plays a pivotal role in cancer growth and metastasis. The aim of this study was to analyse VDR expression of primary breast cancer and corresponding bone metastases tissue samples. Collectively, 15 sample pairs and 11 samples of patients that did not develop metastases were analysed histologically for VDR expression (n = 41). Overall, VDR expression was significantly lower in bone metastases compared to primary tumour samples ( p < .0001). Downregulation of the VDR in breast cancer cells may define a critical turning point in oncogenesis that accelerates cancer cell dissemination and metastases.